2019
DOI: 10.5858/arpa.2018-0316-oa
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Multistep Protocols in the Analysis of Sentinel Lymph Nodes in Cutaneous Melanoma: An Assessment of 194 Cases

Abstract: Context.— Currently, no universal protocol exists for the assessment of sentinel lymph nodes (SLNs) in cutaneous melanoma. Many institutions use a multistep approach with multiple hematoxylin-eosin (H&E) and immunohistochemical stains. However, this can be a costly and time- and resource-consuming task. Objective.— To assess the utility for multistep protocols in the analysis of melanoma SLNs by specifically evaluating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The decision tree intelligent discriminant analysis method is a kind of classification regression tree algorithm (45), which is widely used in medical diagnosis (46), biological analysis (47), deep learning (48) and optical application analysis (49), and also has many applications in data comparative analysis (50) and classification importance analysis (51). In the field of engineering, the decision tree is mainly used in equipment improvement (52), geotechnical engineering special new analysis ( 53), building damage assessment (54), and engineering modeling (55).…”
Section: Introductionmentioning
confidence: 99%
“…The decision tree intelligent discriminant analysis method is a kind of classification regression tree algorithm (45), which is widely used in medical diagnosis (46), biological analysis (47), deep learning (48) and optical application analysis (49), and also has many applications in data comparative analysis (50) and classification importance analysis (51). In the field of engineering, the decision tree is mainly used in equipment improvement (52), geotechnical engineering special new analysis ( 53), building damage assessment (54), and engineering modeling (55).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, institutional protocol for histopathological handling of sentinel lymph nodes and pathological reporting varies widely. 68,128,129,130,131,132 Macroscopically, two main methods of slicing sentinel lymph nodes exists: 'breadloafing', allowing for better examination of the subcapsular region, and bivalving, allowing for better examination of lymphatic vessels. 130,131 Both the European Organisation for Research and Treatment of Cancer (EORTC) and Sydney Melanoma Unit recommend the utilisation of the bivalving technique in sentinel lymph node histopathological and handling protocol.…”
Section: Discussionmentioning
confidence: 99%
“…137 A retrospective study found, utilising a decision tree, that limiting SLN evaluation protocols to two slides of one H&E stain and one Melan-A stain has similar diagnostic accuracy as a protocol incorporating multiple H&E, S100 and HMB-45 stains in addition to those two slides. 132 With the recent discovery that patients who receive CLND do not have a survival advantage over those who undergo observation, further refinement of prognostication is imperative to help improve survival outcomes through determination of appropriate adjuvant treatment beyond observation if necessary. Currently, a 31-gene expression profile (31-GEP) test for cutaneous melanoma has been developed and is currently being evaluated for its utility in clarifying prognosis in AJCC-classified low-risk melanoma and clarifying the wide range of prognosis reported for AJCC stages 2 and 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…HMB-45, Melan-A, S-100, cytoplasmic markers for melanocytes, are frequently used immunocytochemical markers in cytology practice. However, their sensitivity has been demonstrated to be suboptimal, and their expression rates may be lower in metastatic lesions 3,4. SOX10, a nuclear marker, is considered more reliable than cytoplasmic and membranous markers.…”
mentioning
confidence: 99%
“…However, their sensitivity has been demonstrated to be suboptimal, and their expression rates may be lower in metastatic lesions. 3,4 SOX10, a nuclear marker, is considered more reliable than cytoplasmic and membranous markers. Nevertheless, as it may also show positivity in breast carcinoma and spindle cell neoplasms, it should not be used as a sole determinant of melanocytic origin.…”
mentioning
confidence: 99%